Time-dependent accumulation of phenolic compounds in Linum album Kotschy cell culture exposed to methyl jasmonate - Sagharyan, Mostafa; Samari, Elaheh; Sharifi, Mohsen (Biocompounds, 2024)
Linum album can produce many valuable phenolic compounds, especially lignans as the potent anticancer agents. In the present study, we attempted to determine inducing effect of methyl jasmonate (MeJA) (50 µM) as an abiotic elicitor on the production of phenolics such as phenolic acids, flavonoids, and lignans in cell culture of L. album over a period of time. The content of cinnamic acid, p-coumaric acid, and ferulic acid increased at 72 h in response to elicitation. However, the level of caffeic acid increased at 48 h of elicitation, which was 1.53 times higher than the untreated sample. According to the results, the content of flavonoids including catechin, quercetin, myricetin, and daidzein also significantly increased during the last hours of the treatment with 50 µM of MeJA in L. album cells. The maximum levels of quercetin and myricetin were observed at 48 h of elicitation, while catechin and daidzein contents peaked at 72 h, which were 2-fold and 2.42-fold over the control, respectively. Significant time-dependent changes also occurred in lariciresinol (LARI) and 6-methoxypodophyllotoxin (6MPTOX) contents under MeJA treatment, while there was no change in secoisolariciresinol (SECO) content in treated cells compared to the control. The level of 6MPTOX reached 4 times of the control sample after 72 h of elicitation. In conclusion, the induction of phenolics contents in response to MeJA in a time-dependent manner can suggest that treatment time adjustment is essential to increase and obtain specific phenolic compounds in cell culture of L. album at shake-flask scale.